Editorial Introduction - Gordon Wells (Networks: An Online Journal for Teacher Research, 2000)
Once again, this issue features articles by groups of educators who are collaborating to investigate and improve their practice and, in the process, to extend and develop their understanding of the principles underpinning their work. As the increasing number of links to such groups on the Links page attests, collaborative action research is on the increase, as is the number of educators who are experiencing the positive impact it has on their lives.